Harnessing AI for Academic Progress: Common Themes and Future Directions - Juliana Gerard; Kelly Norwood; Muhammad Usman Hadi; Aisling Reid; Antoine Rivoire; Muskaan Singh (Proceedings)
This paper presents a reflection on the workshop topics and on further implications for different subject areas across higher education. We identify five overarching themes which emerged from the workshop presentations and reflect on the discussion of each respective theme. Next, we consider these themes in the contexts of different undergraduate courses across subject areas. We focus on one course each from STEM, Social Sciences, and the humanities (engineering, linguistics, and English, respectively) and identify a component of each course which has been influenced by the increasing presence of generative AI in HE. We link these components to the overarching themes and conclude with some common themes across the subject areas.